Pilgrimage from Darkness : Nuremberg to Jerusalem - Feldman, David E. (Book collections on Project MUSE., 2004)
Oskar Eder was born near Nuremberg in 1925. His youth was influenced by Germany's xenophobic patriotism and Nazi politics. Suffering teenage angst and falling under the sway of the Jungvolk, the younger branch of the Hitler Youth, he was suspicious of his socialist parents' loyalties. He admired older, tougher boys and went on to become a member of the Luftwaffe. During pilot training he discovered that his sheltered small-town life and Nazi propaganda had hidden the fact that something was fundamentally wrong with Germany. After the war he acquired a law degree and b.